2008
DOI: 10.2174/1874437000802010089
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium oxysporum Strains as Potential Striga Mycoherbicides: Molecular Characterization and Evidence for a new forma specialis

Abstract: Fusarium oxysporum isolates (Foxy 2 and PSM197) are potential, highly host specific mycoherbicides for the control of the parasitic weeds Striga hermonthica and S. asiatica. Their target weeds, Striga spp., are major biotic constraints in cereal and legume production in semi-arid tropical Africa, where they adversely affect livelihood of millions of subsistence farmers. The aim of this study was to characterize and sequence the Striga mycoherbicides Foxy 2 & PSM197 in order to more clearly distinguish them fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In Kenya soil, Fusarium oxysporum f. sp. Strigae (Foxy -2) strain as suggested by Avedi et al (2014) was ineffective, need special storage facilities, their perspective has not been entirely utilized (Elzein et al 2008). The strains also release Zearalenone, Trichothecenes and Fumonisin mycotoxins which are believed to be hazardous to animal and human (DMello et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kenya soil, Fusarium oxysporum f. sp. Strigae (Foxy -2) strain as suggested by Avedi et al (2014) was ineffective, need special storage facilities, their perspective has not been entirely utilized (Elzein et al 2008). The strains also release Zearalenone, Trichothecenes and Fumonisin mycotoxins which are believed to be hazardous to animal and human (DMello et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, revealed that some species of Alternaria have the ability to control several weeds that attack crops, for instance, A. cassia accessible as CASST mycoherbicide was used to control sickle weed, A. macrospora was also used to controls Anoda cristate weed in Soybeans (Lawrence et al 2008). In USA, A. macrospora inoculum was used to control jimsonweed (Walker, 2010, Elzein et al 2008). Alternaria sp.…”
Section: Introductionmentioning
confidence: 99%
“…Through molecular characterization of the internal transcribed spacer (ITS) sequence of the ribosomal RNA gene, Elzein et al . (2008) designated a forma specialis to Fusarium oxysporum , known as Fusarium oxysporum f. sp. strigae (Fos).…”
Section: Introductionmentioning
confidence: 99%
“…In North Ghana Fusarium oxysporum isolate Foxy 2 was isolated from a diseased S. hermonthica plant (Abbasher et al, 1995) and a new forma specialis named F. oxysporum f. sp. strigae, which causes Fusarium wilt of Striga species was identified (Elzein et al, 2008). In 2009, the same isolate was imported into Kenya and has been subsequently tested against S. hermonthica.…”
Section: Introductionmentioning
confidence: 99%